Alta mortandad de crias de Fragata Comun provocada por tormenta - Lee, L.=700 1 Osorno, L.
(Es, En)
Ilus., 17 ref.
Keywords: AVES ACUATICAS; MORTALIDAD; FACTORES AMBIENTALES; LLUVIA; MEXICO; FREGATA MAGNIFICENS; FRAGATA COMUN